Incorporation Structural Health Monitoring In The Design Of Slip Formed Concrete Wind Turbine Towers – Progress Report - Hovgaard, Mads Knude (Technical Report Civil and Architectural Engineering, 2013)
<span style="font-family: 'AUPassata-Regular','sans-serif'; font-size: 9pt; mso-bidi-font-family: AUPassata-Regular; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: DA; mso-bidi-language: AR-SA;" lang="EN-US">This report contains introduction to the subject as well as descriptions of the problems, a state-of-art overview, descriptions of the methods applied and of the results achieved so far. Furthermore, the report contains a plan for the remaining part of the project period. In the overall perspective, the project combines many different engineering disciplines and thus the report displays a variety of content. The reliability theory ties the different disciplines together, and the focus is chosen on the dominant uncertainties of the modal damage detection as a consequence barrier (risk reduction by decision rule), as the initial studies in the project indicated this as an interesting and innovative approach